2018
DOI: 10.1007/s00134-018-5222-9
|View full text |Cite|
|
Sign up to set email alerts
|

Epinephrine and short-term survival in cardiogenic shock: an individual data meta-analysis of 2583 patients

Abstract: In this very large cohort, epinephrine use for hemodynamic management of CS patients is associated with a threefold increase of risk of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 129 publications
(87 citation statements)
references
References 37 publications
3
75
0
9
Order By: Relevance
“…Furthermore, a recent meta-analysis with more than 2500 patients found that epinephrine use for hemodynamic management of CS patients was associated with a threefold increase in risk of death (Léopold et al, 2018a(Léopold et al, , 2018b. However, the proportion of post CA patients was only 45%.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent meta-analysis with more than 2500 patients found that epinephrine use for hemodynamic management of CS patients was associated with a threefold increase in risk of death (Léopold et al, 2018a(Léopold et al, , 2018b. However, the proportion of post CA patients was only 45%.…”
Section: Discussionmentioning
confidence: 99%
“…3 The combination of adrenaline with dobutamine, however, portends a particular risk for adverse outcome. 53 In a recent meta-analysis, adrenaline was associated with a three-fold increase in mortality, 54 and in patients with cardiogenic shock after acute myocardial infarction, refractory shock was five-fold more frequent with adrenaline than with NA. 55 For a similar effect on blood pressure, adrenaline (but not NA) increased heart rate (due to its strong b 2 -AR activation; Table 1) and myocardial oxygen consumption (derived from the cardiac double product), increasing lactate as a sign of metabolic compromise.…”
Section: Catecholaminesmentioning
confidence: 99%
“…However, there is a lack of robust outcome data. Evidence for the use of epinephrine in RV failure is equally sparse, however, its use in cardiogenic shock has come under scrutiny as it was recently shown in a large meta-analysis to be associated with increased short-term mortality [70]. One meta-analysis found significant hemodynamic improvements with levosimendan [71], perhaps suggesting an indication in selected patients, but here too there is a paucity of longer-term outcome data.…”
Section: Support Of Inotropy In Rv Failurementioning
confidence: 99%